Heparprotective effect of Bergenia crassifolia extract and silymarinat experimental inhibition of β-oxidation of fatty acids causedby 4-pentenioc acid - D. V. Shutov (Бюллетень сибирской медицины)
The object of this research was to study rat liver bioenergetics at pathology caused by inhibition of β-oxidation of fatty acids against the background of 4-pentenoic acid injection and at silymarin and Bergenia crassifolia extract therapy. The experiment was conducted with 50 nonpedigreed male rats. The functional state of the energy production system was estimated by the polarogaphic method from the rate of oxygen consumption in different Chans metabolic states. At silymarin therapy, increase was observed in the oxidative phosphorylation coupling in all metabolic states. The Bergenia crassifolia extract favored normalization of energy production parameters in rat liver mitochondria more efficiently than silymarint did.